Pengaruh Electronic Word Of Mouth, Harga, Dan Produk Bundling Terhadap Keputusan Pembelian Produk Skincare The Originote - Mei Tiara; Sri Isfantin Puji Lestari; Dian Noor Citra Perdana (STIE Wijaya Mulya, 2026)
This research aims to determine the influence of e-WOM, price and product bundling partially and simultaneously on purchasing decisions for The Originote skincare products. The research method uses quantitative and the population is consumers of skincare products in Solo Raya whose population is unknown. In this research, non-probability sampling was used as a sample and the community used purposive sampling as a sampling technique. Sampling was obtained using a questionnaire. The number of samples used was 97 respondents. Primary data was processed using IBM SPSS Statistics version 26 and secondary data was obtained from the bibliography. This research begins in November 2023. Based on the research instrument test, it was stated that all data were valid and reliable. The results of research using multiple linear regression analysis show that Y = 5.949 + 0,139 + 0,547 + 0,484 + e, on consumer purchasing decisions for original products in Solo Raya. The results of the coefficient of determination test concluded that 47.2% of consumer purchasing decisions for original products were influenced by e-WOM, price and product bundling. Keywords : e-WOM; price; product bundling; purchasing decisions